The Effect of Blended Learning Strategy and Creative Thinking of Students on the Results of Learning Information and Communication Technology by Controlling Prior Knowledge - Resien Resien; Harun Sitompul; Julaga Situmorang (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The purpose of this study is to determine the differences in learning outcomes of ICT subjects between groups of students who are taught with blended learning strategies and expository who have the ability to think creatively after being controlled by initial knowledge. This research method uses quasi experiment with 2x2 factorial design. Data analysis techniques used two-way ANCOVA at a significant level  = 0.05. The results showed that (1) ICT learning outcomes between groups of students taught with blended learning strategies were higher than those of students who were taught with expository learning strategies after controlling for initial knowledge; (2) there is an interaction effect between learning strategies and the ability to think creatively on ICT learning outcomes after controlling initial knowledge; (3) for students who have high creative thinking skills, ICT learning outcomes among groups of students taught with blended learning strategies are higher than those of students who are taught with expository learning strategies after controlling initial knowledge; (4) for groups of students who have low creative thinking ability, ICT learning outcomes among groups of students who are taught expository learning strategies are higher than groups of students who are taught with blended learning learning strategies after controlling for initial knowledge. Based on the results of this study, to improve the learning outcomes of Information and Communication Technology students are done by implementing BL learning strategies with regard to student characteristics.